Characterization of Readmissions Among Patients Enrolled in an Outpatient Parenteral Antimicrobial Therapy (OPAT) Program Over a 2-Year Period at UNC Medical Center. (4th October 2017) - Nwankwo, Onyeka; Eichholz, Anh; Chundi, Vahini; Kinlaw, Alan; Medlin, Tenesha; Fletcher, Lisa; Kufel, Wesley; Farel, Claire; Marx, Ashley
Abstract: Background: The UNC Medical Center OPAT program was started in 2015 to provide multidisciplinary management of medically complex patients referred by the infectious diseases (ID) inpatient services and discharged on parenteral antimicrobials. A primary aim of the program is to avert avoidable readmissions during OPAT therapy through protocolized laboratory monitoring, case review and streamlined access to ID urgent care services. Methods: We abstracted electronic health records for the first 250 patients enrolled in the OPAT program. 223 patients with sufficient recorded data for entire OPAT course were included. All-cause readmission events during OPAT therapy were collected, and cause for readmission was adjudicated by a multidisciplinary committee. Results: Of the 223 patients, 62% were male with median age 53 years (20–88). 39 (17%) experienced a readmission (Table 1). Most readmissions occurred among patients not seen in our OPAT urgent care for the admitting complaint. 57 patients (26%) experienced at least one adverse drug reaction (ADR), e.g., laboratory abnormality, rash, or diarrhea; 7 of these required readmission. ADR was the most common reason for ID urgent care visit. Almost half of readmissions were unrelated to OPAT therapy or OPAT-related diagnosis. Less than 10% of OPAT patients utilized ID urgent care services; none of these visits resulted in readmission. Conclusion: Our OPAT program represents a medically complex cohort that may be at higher risk of readmission at baseline. The availability of providers and pharmacists for urgent care services is effective in avoiding readmission for OPAT-related causes. Future interventions to address common causes of readmission include expanded access to urgent care servvices and close interval follow-up after discharge for particularly high-risk patients. Disclosures: All authors: No reported disclosures.